Change Management and Employee Job Satisfaction : A Case Study of UNMC - Mohan Das, Vasanth Kumar (2015)
Organizational change is a growing area of importance for modern organizations strategic development. Managing effective organizational change processes represents an imperative of success for competitive organizations. This study intends to clarify the relation between perceived influence of organizational change processes on employee job satisfaction, and also, the role of Leadership, corporate communication strategy and human resources management in this relation. The study used both quantitative (Survey) and qualitative (interview) methods. Participants of this study were 104 academic and non-academic employees of UNMC, which voluntarily responded to an online questionnaire composed of measures of Leadership, organizational communication, human resources management, perceived efficacy of organizational change processes and job satisfaction. Data was analysed using the SPSS tool for both descriptive and inferential analysis. In addition interviews were conducted with Chief Executive/Provost of UNMC. Main results showed that Leadership, organizational communication, human resources management exerts a mediational effect in the relation between perceived efficacy of organizational change processes and job satisfaction. Main conclusion is that Change management initiative positively influences job satisfaction of employees of UNMC. Leadership, Human Resource and corporate communication strategy plays an important moderating role in the success of change management initiative and positively influence employee job satisfaction in UNMC. The relevance of the results, recommendations and conclusions are interpreted focusing the impact of organizational change on relevant organizational behaviour dimensions, such as Leadership, Human Resource, Corporate communication strategy and Job satisfaction.